The Impact of Short Video Content in Instagram Reels in Learning English - Datu, Serti Tandi; Allo, Markus Deli Girik; Shilfani, Shilfani; Pratama, Muh. Putra (Jurnal Studi Guru dan Pembelajaran, 2023)
This study investigates the impact of Instagram Reels on English language learning among students of the English Department at Universitas Kristen Indonesia Toraja (UKI Toraja). Recognizing the growing role of digital media in education, the research aimed to explore how students perceive and utilize short video content as a learning tool. A qualitative research design was employed, with participants selected through purposive and snowball sampling to ensure that those interviewed had direct experience engaging with Instagram Reels for learning purposes. Data were collected through semi-structured interviews, which provided detailed insights into students’ experiences, preferences, and reflections on the use of Reels in supporting their English learning. The findings revealed that students frequently interacted with Reels that introduced new vocabulary, demonstrated correct pronunciation, and provided tips for everyday conversation. They emphasized that the short and visually appealing format of Reels made learning more enjoyable and easier to access compared to traditional learning resources. Many participants also noted that the use of humor, subtitles, and real-life contexts in the videos helped them better understand and retain language structures. In addition, students expressed that Reels played a role in boosting their confidence to practice speaking, as the content often provided authentic examples from native or fluent speakers. Despite these positive outcomes, students acknowledged that Instagram Reels should not replace formal instruction. They considered Reels a supplementary tool that supports, rather than substitutes, structured learning activities such as classroom discussions, lectures, and guided practice. The integration of Reels into a broader learning strategy was seen as most effective for enhancing both motivation and skill development. Based on these findings, the study recommends that educators consider integrating social media platforms like Instagram into language learning programs. Such integration has the potential to increase student engagement, foster independent learning, and improve overall learning outcomes.